2014
DOI: 10.1038/srep07299
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Escherichia coli YidC, a membrane protein chaperone and insertase

Abstract: Bacterial YidC, an evolutionally conserved membrane protein, functions as a membrane protein chaperone in cooperation with the Sec translocon and as an independent insertase for membrane proteins. In Gram-negative bacteria, the transmembrane and periplasmic regions of YidC interact with the Sec proteins, forming a multi-protein complex for Sec-dependent membrane protein integration. Here, we report the crystal structure of full-length Escherichia coli YidC. The structure reveals that a hydrophilic groove, form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
133
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(153 citation statements)
references
References 31 publications
15
133
1
1
Order By: Relevance
“…The importance of the cavity was also supported by photo-cross-linking experiments showing that the inner surface of the cavity of SpoIIIJ interacts with substrate protein in vivo (21). Together with the crystal structure of E. coli YidC (22), it is suggested that having a hydrophilic and positively charged cavity is a feature shared by the YidC family members.…”
mentioning
confidence: 56%
“…The importance of the cavity was also supported by photo-cross-linking experiments showing that the inner surface of the cavity of SpoIIIJ interacts with substrate protein in vivo (21). Together with the crystal structure of E. coli YidC (22), it is suggested that having a hydrophilic and positively charged cavity is a feature shared by the YidC family members.…”
mentioning
confidence: 56%
“…The crystal structure of the Gram-negative E. coli YidC was also reported (PDB ID 3WVF) in late 2014 to 3.2 Å by Kumazaki et al (93). Like the Gram-positive B. halodurans structure, the five conserved core TMs are tightly packed in the periplasmic half of the membrane and spread out in the cytoplasmic half (Fig.…”
Section: Recent Insightsmentioning
confidence: 90%
“…Others are found on the exterior region of these TMs as well as in the hydrophilic groove located on other TM segments (93) (Fig. 2).…”
Section: Recent Insightsmentioning
confidence: 99%
“…Crystal structures of YidC proteins from B. halodurans and E. coli (20,40), as well as co-evolution based modeling (27), demonstrate that the large cytosolic loop C1 is folded into a helical hairpin that protrudes from the membrane plane with a tilt determined by an N-terminal proline residue (position 371 within E. coli YidC). Point mutations Y370A and Y377A at the N-terminal end of the loop inactivate YidC in vivo (27), whereas mutations, but not deletions, within the hairpin did not interfere with YidC functionality.…”
Section: Discussionmentioning
confidence: 99%